2020
DOI: 10.21203/rs.3.rs-83186/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeted expression profiling reveals distinct stages of early canine fibroblast reprogramming are regulated by 2-oxoglutarate hydroxylases

Abstract: Background: Ectopic expression of a defined set of transcription factors allows the reprogramming of mammalian somatic cells to pluripotency. Despite continuous progress in primate and rodent reprogramming, limited attention has been paid to cell reprogramming in domestic and companion species. Previous studies attempting to reprogram canine cells have mostly assessed a small number of presumptive canine induced pluripotent stem cell (iPSC) lines for generic pluripotency attributes. However, why canine cell re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Moreover, resulting iPSCs are often poorly characterized and are likely to represent partially reprogrammed cells, as only a few of the canine iPSC publications demonstrate spontaneous in vivo differentiation (i.e., teratoma formation), and the contribution of canine iPSC to chimera formation has not been reported. Finally, although in our hands and others, canine embryonic fibroblasts (CEFs) are reprogrammable; adult fibroblasts remain resistant to OCT4-SOX2-KLF4-MYC (OSKM)-induced reprogramming (11,12). We found that adult fibroblasts have a more restrictive genomic accessibility landscape compared with CEF that "locks" adult cells in their somatic fate and prevents their reprogramming and phenotypic switch (11).…”
Section: Introductionmentioning
confidence: 63%
“…Moreover, resulting iPSCs are often poorly characterized and are likely to represent partially reprogrammed cells, as only a few of the canine iPSC publications demonstrate spontaneous in vivo differentiation (i.e., teratoma formation), and the contribution of canine iPSC to chimera formation has not been reported. Finally, although in our hands and others, canine embryonic fibroblasts (CEFs) are reprogrammable; adult fibroblasts remain resistant to OCT4-SOX2-KLF4-MYC (OSKM)-induced reprogramming (11,12). We found that adult fibroblasts have a more restrictive genomic accessibility landscape compared with CEF that "locks" adult cells in their somatic fate and prevents their reprogramming and phenotypic switch (11).…”
Section: Introductionmentioning
confidence: 63%